Pemanfaatan Simulator Terbang pada Pendidikan Vokasi Penerbang dalam Meningkatkan Minat Bakat Taruna Penerbang - Prayitno, Hadi; Supardam, Dhian; Qiram, Ikhwanul; Shakti Arrafat, Bhima (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
: The purpose of this research is to examine the utilization of flight simulator in Aviation Vocational School and its impact on increasing the interest and talent of cadets. Simulators have become crucial devices in training prospective pilots and provide real-life experience in facing diverse and complex flying situations. A total of 20 first-year cadets were the respondents in this study. The research method used an experimental study, where performance measurements were taken during the initial test, 5, and 10 hours of simulator usage. The test results showed a linear improvement in flying performance with the duration of simulator usage (calculated t-value > table t-value ranging from 0.375 to 0.530). The respondents experienced a relatively high improvement in performance (55.8%) compared to the first hour of usage (25.2%).